Relational teaching: a way to foster EFL learners’ intercultural communicative competence through literary short stories - Gómez Rodríguez, Luis Fernando (Colombian Applied Linguistics Journal, 2014)
This article presents an action research study2 in an advanced EFL class of the language program at a public university in Bogotá, Colombia in 2011. The study suggests that the inclusion of authentic multicultural short stories from the U.S. fosters learners’ critical intercultural communicative competence (ICC) through the implementation of the Relational Teaching approach. The collected data demonstrated that learners developed critical intercultural skills through commonalities (a concept proposed by Relational Teaching) when they read literary short stories. Findings show that applying new teaching approaches and literature in EFL might contribute to create critical intercultural awareness.